2000
DOI: 10.1038/sj.mp.4000696
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific alterations in frontal cortex brain proteins in schizophrenia, bipolar disorder, and major depressive disorder

Abstract: Severe psychiatric disorders such as schizophrenia, bipolar disorder and major depressive disorder are brain diseases of unknown origin. No biological marker has been documented at the pathological, cellular, or molecular level, suggesting that a number of complex but subtle changes underlie these illnesses. We have used proteomic technology to survey postmortem tissue to identify changes linked to the various diseases. Proteomics uses two-dimensional gel electrophoresis and mass spectrometric sequencing of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
274
1
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(300 citation statements)
references
References 43 publications
20
274
1
5
Order By: Relevance
“…Thus, the ability to measure phosphorylated proteins in their native state could facilitate post-mortem investigations of neuropsychiatric disorders. Phosphorylation also effects the migration of proteins during two-dimensional gel electrophoresis (Sickmann and Meyer, 2001), a technique that may be useful for analyzing disease-specific changes in post-mortem brain specimens (Edgar et al, 1999;Fountoulakis et al, 2001;Johnston-Wilson et al, 2000). For these reasons, we investigated the effects of PMI on protein phosphorylation state in mouse brain tissue, where we can control exactly the PMI and are assured minimal genetic/tissue heterogeneity by utilizing inbred strains.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ability to measure phosphorylated proteins in their native state could facilitate post-mortem investigations of neuropsychiatric disorders. Phosphorylation also effects the migration of proteins during two-dimensional gel electrophoresis (Sickmann and Meyer, 2001), a technique that may be useful for analyzing disease-specific changes in post-mortem brain specimens (Edgar et al, 1999;Fountoulakis et al, 2001;Johnston-Wilson et al, 2000). For these reasons, we investigated the effects of PMI on protein phosphorylation state in mouse brain tissue, where we can control exactly the PMI and are assured minimal genetic/tissue heterogeneity by utilizing inbred strains.…”
Section: Introductionmentioning
confidence: 99%
“…DRP-2 is involved in the process of axonal outgrowth mediated by extracellular signals 48 and its expression in the adult brain is suggested to be important as a mechanism of repair and regeneration of adult neurons. 49 Furthermore, depressed levels of this protein have been shown in schizophrenia and Down's syndrome 50,51 and increased levels of DRP-2 carbonyls were detected in brains from Alzheimer's disease patients. 49 DRP-2 is often seen as multiple spots on 2D gels and the ratio between the truncated form and full-length form is suggested to be a biomarker of post-mortem temperature and time.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the proteins differentially expressed in this study have been previously proposed to be associated with the disease. SNAP-25, 28 a synaptic-related protein, metabolic proteins NADH oxidoreductase 29 and CKB, 30 a free radical scavenger SOD, 31 a glial-specific protein GFAP 19 and a trafficking protein, HSP70, 32 are all reported to have altered activity and/or expression levels in schizophrenia. Proteins found to be altered in the ACC gray matter in this study may (a) have a role in schizophrenia and (b) be potential markers of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics, with the ability to investigate the translation of genomic information together with co-and post-translational modifications, 17 offers an approach to studying the global changes in protein expression and modification caused by neuropathologies such as Alzheimer's Disease (AD), Down Syndrome (DS) and schizophrenia. Previous findings of proteomic investigations into schizophrenia include various proteins associated with metabolism and oxidative stress to be differentially expressed in the prefrontal cortex (PFC) in the disease state relative to controls, 18 proteins previously implicated in schizophrenia as well as some novel proteins to be altered in the frontal cortex, 19 and four of 18 altered proteins in the schizophrenia hippocampus mapping to chromosome 6q. 20 In addition, a proteomic study investigating the cerebrospinal fluid (CSF) in schizophrenia identified 54 different gene products, 17 leading to new and refined hypotheses into the molecular mechanisms underlying this disease.…”
Section: Introductionmentioning
confidence: 99%